Does step frequency as a single factor affect running economy? A systematic review - Bernans, E.; Abolins, V.; Lanka, J. (Journal of Human Sport & Exercise, 2023)
Is step frequency (SF) related to running economy and how? This is the main question we have tried to answer in this study. It is a well-known biomechanical variable used in scientific and practical analysis of running technique. A systematic review was carried out to analyse available literature of the field. Scopus, Web of Science and ScienceDirect databases were used for article search. In total 249 articles matched defined queries and after exclusion, 12 were used in the review. After analysis of the review, our hypothesis remained unconfirmed. In some cases, step frequency affected the running economy, while in others it did not have a direct impact on it. It might be that SF cannot be considered in isolation from other biomechanical characteristics and it cannot be analysed as a universal criterion for improving running technique and economy.